EP994 Epigenetic silencing of FBXW7 through promotor hypermethylation in ovarian cancer. (1st November 2019) - Tamimi, Y; Al Hinai, M; Gupta, I; Lakhtakia, R; Al Kalbani, M; Okamoto, A; Al Moundhri, M; Burney, I
Abstract : Introduction/Background: FBXW7, a tumor suppressor gene plays a critical role in cell cycle progression under the regulation of the transcription factor E2 F5 . While FBXW7 is silenced in several cancers; its role in ovarian cancer pathogenesis is still unclear. This study explored FBXW7 promotor methylation status in ovarian cancer and its functional significance. Methodology: FBXW7 expression at mRNA and protein levels were assessed in OVSAHO and MCAS cells using RT-qPCR and western blotting respectively. Expression of FBXW7 was high in MCAS and low in OVSAHO cells. FBXW7 gene methylation status was analyzed in cell lines (MCAS & OVSAHO) as well as in 23 EOC patients (5 normal, 8 benign, 4 borderline, 5 high grade tumors) by both methylation-specific PCR and MS-HRM analysis. Results: In addition to OVSAHO cells, more than 60% of patients analyzed showed methylation. To evaluate its functional importance, FBXW7 expression was restored in OVSAHO cells by treatment with the demethylation agent, 5'-aza-2'deoxycitidine. Western blotting in FBXW7 -restored OVSAHO cells and FBXW7 -positive cell line (MCAS) showed an upregulation in caspases-2, 3, 7, BAX, P53, BAD, Cyclin D1, pNFkB and pGSK3-beta, whereas Bcl-2, Bcl-x, pBad, STAT3, GSK3-beta and NFkB were downregulated; indicating cells to undergo apoptosis via STAT3 pathway. Conclusion: This study described an alternative mechanism for FBXW7 inactivation, namely promoter specific methylation in ovarian cancer and identified FBXW7 as a potential target for guiding the development of therapeutic strategies against ovarian cancer. Disclosure: Nothing to disclose.